La presse italienne, le pouvoir politique et l’autorité judiciaire durant le fascisme - Yannick Beaulieu (Amnis)
The role of the Italian press has been a crucial political issue from the end of the First World War onwards. Italian newspapers responded to, and in some cases created, all the political struggles which divided society in the immediate aftermath of the war, in part resulting in the rise of power of the fascists. There were, at that time, as many newspapers as there were political parties and organisations. Articles were explicitly violent and the civil war was started by various campaigns run by political newspapers. The most intense period of conflict was between 1920 and 1926, at which time the offices of left-wing newspapers were regularly being burnt down by fascist groups. The role played by the judiciary is also an important issue, with judges failing both to restore public safety or to maintain impartiality. Relation between judges and the newspapers were ambiguous. On one hand, left-wing parties viewed the judiciary as a bourgeoisie-closely allied to the government; on the other hand, the fascist groups published blacklists containing the names of Judges they claimed were too weak in dealing with left-wing activists or too biased against fascist defendants. The Giacomo Matteotti case was a turning-point in the consolidation of the Benito Mussolini’s power, using the crisis, he transformed Italy into a totalitarian regime: with all opposition newspapers banned and fascists publications kept under strict control. Simply put, newspapers became nothing more or less than tools for state-led propaganda.